Conjugated Oligomers as Fluorescence Marker for the Determination of the Self-Healing Efficiency in Mussel-Inspired Polymers - Ahner, Johannes; Pretzel, David; Enke, Marcel; Geitner, Robert; Zechel, Stefan; Popp, Jürgen; Schubert, Ulrich S.; Hager, Martin D. (Chemistry of Materials, 2018)
Within the current study, a novel approach for the detailed determination of the scratch healing efficiency in mussel-inspired polymer films is presented. For this purpose, a sensor molecule was incorporated into a self-healing polymer network based on reversible zinc-histidine interactions. The fluorescence of the sensor molecule was monitored enabling a detailed depth- and time-resolved determination of the healing efficiency by means of confocal laser scanning microscopy (CLSM). Finally, this concept represents an efficient and detailed approach for the determination of the scratch self-healing efficiency in polymer films and can also be applied for other scratch self-healing systems, which are based on reversible dynamic bonds.
CRIS-Team Scopus Importer:2023-04-20